Healthy Eating: Improve Nutrition with SNAP - Linda B. Bobroff (EDIS)
SNAP (the Supplemental Nutrition Assistance Program, formerly called Food Stamps) is one of several nutrition programs that help people meet their dietary needs. This 2-page fact sheet provides a brief overview of SNAP and examples of ingredients for healthy meals. Written by Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, revised November 2016.http://edis.ifas.ufl.edu/fy918